Aplikasi konsep Hifz Al-Din dalam pengurusan perniagaan patuh syariah (Application of the concept of Hifz Aldin in shariah-compliant business management) - Anas, Mohd Yunus; Mohammad Normaaruf, Abd Hamid (2020)
A business that adheres to Islamic law is a business that operates with honesty and not doing any form of prohibited things in Islam. Maqasid Shariah is the basic standard for mankind in doing something towards creating a Shariah-compliant way of life, including in business. Religion is the main aspect that must be emphasized in performing business. Islam is a religion that must be preserved, maintained and expanded by all Muslims. Islam strongly encourages Muslims to get involved in all sort of business, to earn a living and improved livelihoods to mankind, as long as it meets the Quran and al-Sunnah’s standards. Hifz al-Dīn concept is still not taken seriously in a business management. The issues related to religion, such as riba, employees not performing obligatory prayers and unethical attire are still not stress seriously in business operations. Thus, hifz al-Dīn is an important concept in making sure the business carried out complies with the requirements of Islamic legislation. The purpose of this article is to give exposure in implementing hifz al-Dīn concept. This article studies use qualitative methods by using content analysis of materials related to Islamic Maqasid and businesses. As a result, performing obligatory prayers, trades of halal products, shariah compliant dress code and Islamic financial management need to be taken seriously in every business operations in order to make sure it is in line with the requirements of Islamic law based on hifz al-Dīn concept.